1993
DOI: 10.1007/bf02482398
|View full text |Cite
|
Sign up to set email alerts
|

Approximate solution for kinetic differential equations

Abstract: In the present work we show the analysis of an approximate solution for the coupled kinetic differential equations of a defect involving processes of untrapping, retrapping and recombination annihilation, using the Poincar~-Dulac theorem.PACS 82.20.Wt -Computational modeling: simulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Previous research findings have shown that the solutions for the non-linear stability analysis of equations 1a and 1b are stable, following a hyperbolic path [18]. Mizukami et al [19] observed that these solutions can be represented by the sum of two terms. The first term leads to slow first order decay and the other to a fast decay.…”
Section: P P Pmentioning
confidence: 99%
“…Previous research findings have shown that the solutions for the non-linear stability analysis of equations 1a and 1b are stable, following a hyperbolic path [18]. Mizukami et al [19] observed that these solutions can be represented by the sum of two terms. The first term leads to slow first order decay and the other to a fast decay.…”
Section: P P Pmentioning
confidence: 99%